The peculiarities of sports training organization among 15-16-year-old racing skiers - Batalov, A. G.; Nikonov, S. E.; Burdina, M. E. (The Russian Journal of Physical Education and Sport, 2022)
The main objectives of the research were in effective parameters of sport load determination using special-preparatory orientation means in a yearly cycle of 15-16-year-old racing skiers. Materials. The research was carried out during sport seasons 2020/21 and 2021/22 among the racing skiers of the 1st sport category (20 people). They are included into the national team of the Vladimir region. Research methods. The received results were analyzed in terms of the existing normative documents (the Federal Standard of Sports Training (FSST)), model programs [4] and a generalized model of general volume of cyclic load dynamics in training sports reserve in cross-country skiing [5]. We also analyzed the main relief parameters of the training and competitive routes and the dynamics of the experimental group participants competitive effectiveness during the studied period, mathematical statistics methods were also used. Results. The research results showed that in cross training we see less volume of the load fulfillment in reference to model program and the generalized model. In other means of training the participants of the experimental group fulfilled greater volume of the load: in skiroller training for 862 km and 728 km, in ski training - for 233 km and 74 km. General volume of cyclic load was 5200 km. It is 900 km more than relatively approximate program and 400 km more than relatively generalized model. The authors consider that the increased volume of skiroller training, mainly realized in "home" conditions of the Vladimir region on plain-hilly (d=about 5m/km) and cross country routs (d=6-14m/km), decreases the training effect. We also underline unjustified volume decrease in cross and cross with skating steps imitation on the slopes. Cross running and imitation exercises on the slopes help to model physiological tension of an athlete's organism, adequate to competitive activity and in this condition become an effective means of specialized training. The effectiveness of training the respondents from the experimental group is proved by their competitive effectiveness improvement in races during the Ivanovo Region Championship during the following periods of sports seasons: 2020/21 and 2021/22. In classical style racing relative result increase was 5,88%, in skating style racing - 10,44%, general competitive effectiveness increased for 8,9%. It is mentioned that two athletes from the experimental group fulfilled the control normative Candidate Master of Sports. It is necessary in order to transfer on the stage of sportsmanship improvement. Conclusion. Further quality of sports training improvement is conditioned by natural dynamics of general volume of cyclic load increase and the balanced ratio of special-preparatory orientation training means. The relief of the training routs, adequate to the oncoming competitive activity, is considered as an important factor in the effectiveness of sports training increase.